2014
DOI: 10.1155/2014/828149
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect onIn VitroLDL Oxidation and HMG Co-A Reductase Activity of the Liquid-Liquid Partitioned Fractions ofHericium erinaceus(Bull.) Persoon (Lion’s Mane Mushroom)

Abstract: Oxidation of low-density lipoprotein (LDL) has been strongly suggested as the key factor in the pathogenesis of atherosclerosis. Mushrooms have been implicated in having preventive effects against chronic diseases due especially to their antioxidant properties. In this study, in vitro inhibitory effect of Hericium erinaceus on LDL oxidation and the activity of the cholesterol biosynthetic key enzyme, 3-hydroxy-3-methyl glutaryl coenzyme A (HMG Co-A) reductase, was evaluated using five liquid-liquid solvent fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 65 publications
0
52
0
Order By: Relevance
“…118 Of the solvent extractions, the hexane fraction showed the highest inhibition of oxidation and strongly inhibited the activity of the enzyme by up to 59.9% at 10 mg/mL. GC-MS analysis revealed that this fraction contained ergosterol and linoleic (9,12-octadecadienoic) and octadecanoic acids, suggesting that these components and possibly also a polysaccharide (not evaluated) might be responsible for the observed antioxidative properties of the mushroom extract and that the hexane extract might help to prevent oxidative stress-induced pathogenesis of atherosclerosis.…”
Section: ■ Beneficial Effects On Ischemiamentioning
confidence: 99%
“…118 Of the solvent extractions, the hexane fraction showed the highest inhibition of oxidation and strongly inhibited the activity of the enzyme by up to 59.9% at 10 mg/mL. GC-MS analysis revealed that this fraction contained ergosterol and linoleic (9,12-octadecadienoic) and octadecanoic acids, suggesting that these components and possibly also a polysaccharide (not evaluated) might be responsible for the observed antioxidative properties of the mushroom extract and that the hexane extract might help to prevent oxidative stress-induced pathogenesis of atherosclerosis.…”
Section: ■ Beneficial Effects On Ischemiamentioning
confidence: 99%
“…Our in vitro tests included DPPH free-radical scavenging effects, total polyphenol content through the Folin-Ciocalteu assay, lipid peroxidation inhibitory test, and human low-density lipoprotein (LDL) oxidation inhibitory test. [25][26][27][28] The inhibitory effects of the fractions and of the G. lucidum HWE were also tested. 29…”
Section: B In Vitro Studiesmentioning
confidence: 99%
“…The composition of the vitamin mixture in the diet was as follows (in g/100 g vitamin mixture): 9.5 × 10 −4 g retinyl acetate, 1.2 × 10 −3 g cholecalciferol, 0.05 g α-tocopherol acetate, 2.4 g thiamine HCl, 2.4 g riboflavin, 12.0 g nicotinic acid, 9.6 g D-calcium pantothenate, 1.2 g pyridoxine HCl, 9.5 × 10 −2 g folic acid, 0.25 g vitamin K, 9.5 × 10 −3 g cyanocobalamine, 47.95 g inositol, and 24.0 g ascorbic acid. The composition of the mineral mixture added to the diet was as follows (in g/100 g vitamin mixture): 28…”
Section: Animals and Maintenancementioning
confidence: 99%
“…: hericenones (C-H), a group of aromatic compounds isolated from the fruiting body; and erinacines (A-I), a group of cyathane-type diterpenoids found in the mycelium. 18 Both groups of substances easily cross the blood-brain barrier, and have been found to have neurotrophic and in some cases neuroprotective effects. 19 Erinacines (A-I) have demonstrated induction of nerve growth factor (NGF) synthesis.…”
Section: Terpenoids: Sesterpenes and Diterpenoidsmentioning
confidence: 99%